ARE FUTURE SOCIAL WORKERS OF BACHELOR DEGREE READY TO PROVIDE INTEGRATED SOCIAL SERVICES IN THE TERRITORIAL COMMUNITY IN UKRAINE - Slozanska, Hanna (Social work and education, 2018)
The development of effective and efficient mechanisms for the integrated social services providing to individuals/families in need is one of the state's priorities due to the government reform of decentralization implementing, which involves the transfer of a significant share of powers in the field of social welfare of the population to the newly established united territorial communities. Recruitment and employment in the communities qualified social workers, able to provide the social services to people in need are the priority task of the executive bodies of the united territorial communities. At the same time, under such conditions, there is a need to evaluate the readiness of bachelor's programs in social work graduates to work in the united territorial communities and provide integrated social services to those who need them. The data reseaived as a result of the analysis will form the basis for the development of appropriate content-technological and teaching, methodological support, which in the process of professional training of future social workers in the HEIs will contribute to the formation of the mentioned readiness and will allow rethinking the concept of future social workers training in the HEIs of Ukraine in order to train specialists "suitable" to work in new conditions that dictates the labor market.